Loneliness and Risk of Incident Hearing Loss: The UK Biobank Study - Yunlong Song; Andrew Steptoe; Honghao Yang; Zheng Ma; Lizhi Guo; Bin Yu; Yang Xia (Health Data Science)
Background: Hearing loss (HL) is one major cause of disability and can lead to social impairments. However, the relationship between loneliness and the risk of incident HL remains unclear. Our study aimed to investigate this association among adults in the UK. Methods: This cohort study was based on data from the UK Biobank study. Loneliness was assessed by asking participants if they often felt lonely. Incident HL was defined as a primary diagnosis, ascertained via linkage to electronic health records. Cox proportional hazard regression models were used to examine the association between loneliness and risk of incident HL. Results: Our analyses included 490,865 participants [mean (SD) age, 56.5 (8.1) years; 54.4% female], among whom 90,893 (18.5%) reported feeling lonely at baseline. Over a median follow-up period of 12.3 years (interquartile range, 11.3 to 13.1), 11,596 participants were diagnosed with incident HL. Compared to non-lonely participants, lonely individuals exhibited an increased risk of HL [hazard ratio (HR), 1.36; 95% confidence interval (CI), 1.30 to 1.43]. This association remained (HR, 1.24; 95% CI, 1.17 to 1.31) after adjusting for potential confounders, including age, sex, socioeconomic status, biological and lifestyle factors, social isolation, depression, chronic diseases, use of ototoxic drugs, and genetic risk of HL. The joint analysis showed that loneliness was significantly associated with an increased risk of incident HL across all levels of genetic risks for HL. Conclusions: Loneliness was associated with the risk of incident HL independent of other prominent risk factors. Social enhancement strategies aimed at alleviating loneliness may prove beneficial in HL prevention.